Skrining Fitokimia dan Uji Antioksidan Fraksi Etil Asetat Dari Ekstrak Etanol Daun Kunyit (Curcuma longa L.) Dengan Metode DPPH - Julia Megawati Djamal; Hana Rindi Sahea; Agust A Laya (STIKes Ibnu Sina Ajibarang, 2025)
Turmeric leaves (Curcuma longa L.) is a traditional medicinal plant that contains secondary metabolites such as flavonoids, tannins, and alkaloids, which have potential as natural antioxidants. This study aims to identify the secondary metabolite content and evaluate the antioxidant activity of the ethyl acetate fraction of the ethanol extract of turmeric leaves using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Extraction was carried out using the maceration method with 96% ethanol as the solvent, followed by liquid-liquid fractionation using ethyl acetate. Qualitative phytochemical screening was performed to detect the presence of bioactive compounds such as alkaloids, flavonoids, tannins, saponins, and steroids, while antioxidant activity was assessed by observing the color change of the DPPH solution. The results showed that the ethyl acetate fraction contained these secondary metabolites and exhibited antioxidant activity, as indicated by a color change from purple to yellow. In conclusion, the ethyl acetate fraction of the ethanol extract of turmeric leaves contains bioactive compounds and has potential as a natural antioxidant source.